Neoadjuvant intra-arterial chemotherapy using an original four-lumen double-balloon catheter for locally advanced uterine cervical cancer - Tanaka, Tomohito (Oncotarget, 2018)
OBJECTIVE: We report a balloon-occluded arterial infusion therapy with an original four-lumen double-balloon catheter (4L-DB) which allows for the efficient injection of an anticancer agent at a high concentration to the target spot for patients with locally advanced uterine cervical cancer. METHODS: One hundred and forty-three patients with locally advanced cervical cancer treated with neoadjuvant intra-arterial chemotherapy (NAIAC) or a primary radical hysterectomy (PRH) were retrospectively assessed. The patients in the NAIAC group received irinotecan 70 mg/m2 intravenously on day 1 and 8 and cisplatin 70 mg/m2 intra-arterially using the 4L-DB on day 2 of a 21-day course, and two courses were performed in principle. The radical hysterectomy was performed within 6 weeks after NAIAC. RESULTS: Ninety-four patients were treated with NAIAC, and 49 patients undertook a PRH. The response rate of NAIAC on MRI was 92.6%. Fourteen patients (14.6%) had no evidence of cancer cells on pathologic diagnoses. The NAIAC group had a longer disease-free survival than the PRH group (p=0.02); however, the overall survival was not significantly different. The relative risk (RR) for recurrence was higher in patients with lymph node metastasis (RR, 4.31; 95% CI, 2.23-8.43) and lower in those who underwent NAIAC (RR, 0.30; 95% CI, 0.14-0.68). CONCLUSION: Our results with NAIAC using the 4L-DB catheter in locally advanced cervical cancer indicates beneficial effects on primary lesions and improves disease-free survival.